When Echinococcus granulosus transmigrates from the liver into the pericardium: a case report. Issue 2 (9th February 2021) - Kuemmerli, Christoph; Sánchez-Velázquez, Patricia; Tschuor, Christoph; Oberkofler, Christian; Lachat, Mario; Müllhaupt, Beat; Clavien, Pierre-Alain; Petrowsky, Henrik
Abstract: Infection with Echinococcus granulosus is a common helminthic disease worldwide with endemic in a region with high endemic areas in Africa, Asia, Middle East, South America and southern Europe. We report a rare case of a young patient with cystic echinococcal disease of the liver invading the pericardium. The patient initially presented with life-threatening cardiac tamponade, which resulted in the discovery of the underlying parasitic disease. He successfully underwent en-bloc hepatic pericystectomy and pericardiac resection with closure of the pericardial defect using a xenogeneic patch. After this procedure, he recovered well and had no cardiac complications in the long term. Under treatment with albendazol, the patient showed no signs of recurrent disease. Cases of complex cystic echinococcosis, which invade adjacent organs or body cavities, often need radical surgery for definitive treatment embedded in a multidisciplinary approach in highly specialized centers.